Monitoring of serum and urinary biomarkers during treatment of canine visceral leishmaniasis - Alvaro Felipe de Lima Ruy Dias; Eveline da Cruz Boa Sorte Ayres; Fernanda Harumi Maruyama; Bruna Ribeiro Gomes Monteiro; Maria Sabrina de Freitas; Arleana do Bom Parto Ferreira de Almeida; Adriane Jorge Mendonça; Valéria Régia Franco Sousa (Veterinary World, 2020)
Background and Aim: Canine visceral leishmaniasis (CanL) has a broad spectrum of changes, with kidney disease being considered the main cause of mortality. Thus, this study aimed to monitor serum and urinary biomarkers in response to two short-term treatments for CanL.